Fate of polycyclic aromatic hydrocarbons from the North Pacific to the Arctic: Field measurements and fugacity model simulation. (October 2017) - Ke, Hongwei; Chen, Mian; Liu, Mengyang; Chen, Meng; Duan, Mengshan; Huang, Peng; Hong, Jiajun; Lin, Yan; Cheng, Shayen; Wang, Xuran; Huang, Mengxue; Cai, Minggang
Abstract: Polycyclic aromatic hydrocarbons (PAHs) have accumulated ubiquitously inArctic environments, where re-volatilization of certain organic pollutants as a result of climate change has been observed. To investigate the fate of semivolatile organic compounds in the Arctic, dissolved PAHs in the surface seawaters from the temperate Pacific Ocean to the Arctic Ocean, as well as a water column in the Arctic Ocean, were collected during the 4th Chinese National Arctic Research Expedition in summer 2010. The total concentrations of seven dissolved PAHs in surface water ranged from 1.0 to 5.1 ng L −1, decreasing with increasing latitude. The vertical profile of PAHs in the Arctic Ocean was generally characteristic of surface enrichment and depth depletion, which emphasized the role of vertical water stratification and particle settling processes. A level III fugacity model was developed in the Bering Sea under steady state assumption. Model results quantitatively simulated the transfer processes and fate of PAHs in the air and water compartments, and highlighted a summer air-to-sea flux of PAHs in the Bering Sea, which meant that the ocean served as a sink for PAHs, at least in summer. Acenaphthylene and acenaphthene reached equilibrium in air-water diffusive exchange, and any perturbation, such as a rise in temperature, might lead to disequilibrium and remobilize these compounds from their Arctic reservoirs. Graphical abstract: Highlights: A general decreasing trend of PAHs was observed from the North Pacific to the Arctic. Hydrological stratification and particle settling both controlled the depth profiles of PAHs. The fugacity model highlighted air-to-sea net diffusive fluxes of PAHs.